Surface properties modification of magnesium alloys by low energy high current pulsed electron beam; Surface and Coatings Technology; Vol. 420 - Morini F. Federico; Bestetti M. Massimiliano; Franz S. Silvia; Vicenzo A. Antonello; Markov A. B. Aleksey Borisovich; Yakovlev E. A. Evgeny Aleksandrovich (2021, 2021)
Title screen